Environmental Factors Affecting Near-Surface Oxygen Content Vary in Typical Regions of the Qinghai-Tibet Plateau - Liu, Dong; Tang, Haiping (Frontiers in Environmental Science, 2022)
Hypoxia threatens the health of people in highland regions around the world. Recent studies have shown that altitude has a significant effect on near-surface oxygen content at large geographic scales, and whether this effect is manifested at the landscape scale, particularly on the Qinghai-Tibetan Plateau (QTP) in China, has not been documented. We investigated the relationship between altitude, vegetation (Net Primary Productivity, NPP; Leaf Area Index, LAI; Fractional Vegetation Cover, FVC; Length of the Growing Season, LOS and Vegetation Type), climate variables (Mean Monthly Temperature, MMT and Mean Monthly Precipitation, MMP), and near-surface oxygen content in five typical regions of the QTP, including the Qilian Mountains (QLM), the Three-River Headwater Area (THA), Ngari Prefecture (NAP), Hengduan Mountains (HDM) and Yajiang Valley (YJV). The results showed that (1) altitude, NPP, FVC, LOS, MMP and MMT were important variables for predicting near-surface oxygen content; (2) the local-scale relationship between altitude and oxygen content exhibited negative or no correlations across broad regions; and (3) oxygen content exhibited a great deal of spatial heterogeneity, with altitude being the main affecting factor, followed by vegetation. Different drivers of near-surface oxygen content should be incorporated into Earth system models to reduce uncertainty in predicting oxygen dynamics and its potential feedback to global warming.